2022
DOI: 10.1021/acsami.2c01597
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Strong Electrically Insulated Nanopapers with High UV Resistance Derived from Aramid Nanofibers and Cellulose Nanofibrils

Abstract: Aramid nanofibers (ANFs) have great potential for civil and military applications due to their remarkable mechanical modulus, excellent chemical reliability, and superior thermostability. Unfortunately, the weak combination of neighboring ANFs limits the mechanical properties of ANF-based materials owing to their inherent rigidity and chemical inertness. Herein, high-performance nanopapers are fabricated by introducing a tiny amount of cellulose nanofibrils (CNFs) to serve as reinforcing blocks via vacuum filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…The excellent mechanical properties thanks to chitosan demonstrated in uniaxial tensile experiments were also confirmed during crack propagation (Figure S14). It is worth mentioning that the addition of supersaturation led to agglomeration in the fiber network, which weakened the mechanical properties. , The Lagrange strain fields in the Y direction (ε yy ) for C-ANF networks of 7.5 wt % chitosan in the crack propagation process were calculated (Figure c). The 2D-DIC algorithm used in this paper was based on the subregion deformation.…”
Section: Resultsmentioning
confidence: 99%
“…The excellent mechanical properties thanks to chitosan demonstrated in uniaxial tensile experiments were also confirmed during crack propagation (Figure S14). It is worth mentioning that the addition of supersaturation led to agglomeration in the fiber network, which weakened the mechanical properties. , The Lagrange strain fields in the Y direction (ε yy ) for C-ANF networks of 7.5 wt % chitosan in the crack propagation process were calculated (Figure c). The 2D-DIC algorithm used in this paper was based on the subregion deformation.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the strong interfacial interaction between ANFs and MMT as well as the mechanical interlocking network among ANFs in AT layers led to the crack of the “pull-out” mode of fibers. 41 Interestingly, hierarchical zigzag cracks could absorb lots of fracture energy in the crack propagation process, and the “pull-out” process of ANFs also absorbs vast energy and effectively prevents the cracks propagation. 42 This results in the significant improvement of strength and toughness of the AT3@MX2 nanocomposite.…”
Section: Resultsmentioning
confidence: 99%
“…The other way is introduction of nanofibers into the paper. [22][23][24] Yang et al [23] found that para-aramid paper containing 6 wt% para-aramid nanofibers had a 44.1% higher breakdown strength than the original paper. Although these methods have improved the performance of aramid paper, there are still some unavoidable problems.…”
Section: Introductionmentioning
confidence: 99%